Factors influencing bank selection decision in Nepal - Wagle, Sudip (Patan Prospective Journal, 2022)
Banking services play an important role in the operation of a corporate institution by enabling the safe flow of money from one party to another, trade financial deals, risk mitigation, cash flow management services, and even offering security services to improve relationships between banking institutions, clients, and partners. However, unhealthy competition between them it makes confusion to select the right one. This study aims to identify the factors influencing bank selection decision by using a set of dependent (bank selection decision) and independent variables (service convenience, bank charges, bank reputation and employee behavior). This study is based on 200 respondent of banks customers using simple random sampling method. The descriptive and causal-comparative research design was employed. Both descriptive and inferential statistical tools have been used. The results revealed that service convenience and bank charges have a significant positive association with the bank selection decision. The bank reputation has a negative and employee behavior has a positive but both have insignificant impact on bank selection decision. The finding of this study is valuable to the probing customers, concerned bankers, academicians and government authorities and future researcher, which help them to more concern towards their customers in future.